1998
DOI: 10.1053/euhj.1997.0804
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the postoperative period and surgical procedure on ambulatory blood pressure-determination of hypertension load after successful surgical repair of coarctation of the aorta

Abstract: Aims This study quantified hypertension load using 24-h ambulatory blood pressure monitoring after successful repair of coarctation of the aorta less than (1) or more than 10 years previously (2) and examined the influence of the surgical procedure (anastomosis or subclavian flap). Methods and ResultsAmbulatory blood pressure recordings were obtained using an Accutracker II monitor every 30 min during the day and hourly, at night. Day and night systolic and diastolic values were higher in coarctation of the ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…End to end anastomosis had been used in nine patients and left subclavian flap angioplasty in one. Calculation of blood pressure loads as previously reported3 showed that patients had a similar daytime prevalence of systolic and diastolic hypertension (14 (5)% and 1.5 (1)%) as controls (12 (4)% and 1 (0.5)%). Electrocardiographic and echocardiographic variables were normal in all patients.…”
Section: Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…End to end anastomosis had been used in nine patients and left subclavian flap angioplasty in one. Calculation of blood pressure loads as previously reported3 showed that patients had a similar daytime prevalence of systolic and diastolic hypertension (14 (5)% and 1.5 (1)%) as controls (12 (4)% and 1 (0.5)%). Electrocardiographic and echocardiographic variables were normal in all patients.…”
Section: Methodssupporting
confidence: 53%
“…A notable increase in the prevalence of systolic hypertension is further observed for post-surgical periods greater than 10 years 12 Using 24 hour ambulatory blood pressure monitoring, we have recently shown that daytime systolic hypertension was present in 49% of recordings from patients successfully operated on more than 10 years previously for coarctation of the aorta, compared with 20% of recordings in patients with a shorter postoperative period 3. In the absence of recoarctation or other complication, a clear explanation for this higher incidence of hypertension after repair of coarctation is still lacking.…”
mentioning
confidence: 99%
“…The studies that have been carried out using this technology (table 3) found a significantly higher mean 24 hour blood pressure in coarctation patients than in controls. [20][21][22][23][24][25] Some of these studies have used control data from the literature to define hypertension using the 24 hour blood pressure results and the prevalence of hypertension varies in these studies from 19-45%. However, these studies are of selected patients and cannot be used as a reliable measure of the prevalence of hypertension in this population.…”
Section: Discussionmentioning
confidence: 99%
“…111 However, many recommend exercise or ambulatory blood pressure monitoring, despite questions regarding its predictive value and clinical relevance postcoarctation repair 127,128 because hypertension is frequently found even if normotensive at rest. 9,26,38,51,77,[129][130][131] Although systolic parameters are the most frequently used in the literature, there is mounting evidence for diastolic dysfunction in coarctation, which is associated with left ventricular hypertrophy. 50,60 It is known that stent placement reduces the increased end diastolic pressures and trend toward left ventricular hypertrophy.…”
Section: Primary Successmentioning
confidence: 99%